SURVEY OF BOVINE MASTITIS IN DAIRY HERDS IN RIBEIRÃO PRETO, SÃO PAULO STATE, BRAZIL - KOBORI, D.; RIGOBELO, E. C.; MARIN, J. M.; ÁVILA, F. A. (Ars Veterinaria, 2008)
The purpose of this study was to isolate pathogens from the quarter milk of cows udders from different dairy herds and to identify the different genera and species involved in mastitis. A total of 528 milk samples from clinical and subclinical mastitis quarters from five dairy herds of Ribeirão Preto, São Paulo State, Brazil, were included in this survey. Staphylococci was the largest group of pathogens isolated. Antibiotic resistance was found to be high between the major pathogens, especially to lincomycin (73.6-100.0%), penicillin (61.9- 100.0%), novobiocin (64.2-100.0%), trimethoprim-sulphadyazin (71.0-100.0%). Multidrug resistance was a common event for the isolates. KEY-WORDS: Bovine mastitis. Antibiotic resistance. Escherichia coli. Staphylococcus sp. Streptococcus sp.